The Arthroscopic Application of Radiofrequency in Treatment of Articular Cartilage Lesions - Lin, Chaosheng; Deng, Zhenhan; Xiong, Jianyi; Lu, Wei; Chen, Kang; Zheng, Yizi; Zhu, Weimin (Frontiers in Bioengineering and Biotechnology, 2022)
Articular cartilage lesion is a common disease to be treated by arthroscopic surgery. It will eventually progress to osteoarthritis without proper management, which can affect patients’ work and daily life seriously. Although mechanical debridement and laser have been used clinically for its treatment, due to their respective drawbacks, radiofrequency has drawn increasing attention from clinicians as a new technique with more advantages. However, the safety and efficacy of radiofrequency have also been questioned. In this article, the scope of application of radiofrequency was reviewed following an introduction of its development history and mechanism, and the methods to ensure the safety and effectiveness of radiofrequency through power and temperature control were summarized.